Język a kultura – rozwijanie świadomości interkulturowej u uczniów dorosłych: optymalne warunki dydaktyczne - Król, Werona (Neofilolog, 2019)
Since language is an integral part of culture, we may say that language is its carrier. Consequently, in order to fully participate in the social life it is not enough to be a proficient language speaker. What we need is the knowledge of particular customs which, to certain extent, can be acquired during inter-cultural communication classes. Therefore, FL teachers should try to devel-op intercultural awareness in their students, so that they could avoid stress-ful situations and misunderstandings in communication. It is particularly important in the case of adult learners who have already developed routine models of behaviour expected in their motherland.